Big Data Analysis Of Banten Community Information Consumption After The Decline of The Covid 19 Case - Darwis Sagita; Burhanudin Mujtaba; Rahmi Winangsih (LONTAR: Jurnal Ilmu Komunikasi, 2023)
This research explains the information consumption of Banten people after the decline of the covid 19 case. What information themes are communicated by the community about Banten on social media. This research was conducted with a qualitative approach by discussing the results of data mining searches (data retrieval on social media through applications), while the application used is NodeXL. The following are the results of this study; among the five aspects of information that researchers examined the data (health, education, economy, tourism, and politics), health information was the least communicated (both one-way and two-way) by the community. Meanwhile, politics and tourism are the most communicated aspects of social media. It can be said that the communication behavior of the community about Banten Province on YouTube social media is generally not dominated by two-way or more communication models. Feedback only occurs on certain information themes. The theme of political information and tourism is the most two-way or more. Meanwhile, health information is the least discussed and does not generate much feedback. It can be concluded that health information is no longer a public concern after the decline in covid 19 cases.